The Effect of Riau Malay Culture (Budi Sdayu)-Based Digital Books to Improve Prosocial Behaviour of 5 to 6-Year-Old Children in Public Kindergarten Pembina 02 Kampar - Baiatun Nisa, Afra; Risma, Devi; Kurnia, Rita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to test the effect of Riau Malay Culture-based Digital Books (BuDi SDaYU) on improving the prosocial behaviour of children aged 5-6 years at Pembina 02 State Kindergarten Kampar. Using a quantitative approach with a true experimental design of the pretest-posttest control group design, 46 children were randomly divided into experimental and control groups. The research instrument was a prosocial behaviour observation sheet, with data analysis using an independent sample t-test and a paired sample t-test. The results of the paired t-test in the experimental class reveal a significant increase (t count = 26.184; Sig. 0.000 <0.05), and the posttest comparison between groups reveals a significant difference (t count = 8.400; Sig. 0.000 <0.05). The normalised gain value of 63.40% indicates the effectiveness of BuDi SDaYU in the moderate category. Thus, it can be concluded that this media is effective for the prosocial behaviour of early childhood through integrating Riau Malay cultural values.